Outcomes and limitations of hospital-based newborn hearing screening. (July 2017) - Kim, Shin Hye; Lim, Jae Hyun; Han, Jae Joon; Jin, Young Ju; Kim, Sun Kyung; Kim, Jin Young; Song, Jae-Jin; Choi, Byung Yoon; Koo, Ja-Won
Abstract: Objectives: Globally, newborn hearing screening (NHS) is variably incorporated into national healthcare systems. The authors reviewed the set-up and evolution process of a hospital-based NHS program in South Korea, where screening costs for low-income families are paid by the National Health Authority. Methods: The NHS process for 13805 newborns delivered in a tertiary referral center of South Korea from 2005 through 2014 was reviewed. Hearing screening was conducted using automated auditory brainstem response (AABR); hearing loss was confirmed by auditory brainstem response for newborns who did not pass the screening test. Results: The mean screening rate for hearing loss was 53.6% (7403 of 13805 newborns), which plateaued at 79.6% over time. Of the 14806 ears (7403 newborns), 1030 (7.0%) were assessed as "refer" on the first AABR, with 204 (1.4%) being assessed as "refer" on the second AABR. In hearing confirmation tests, 74 infants (1.0% of 7403 newborns) were diagnosed with hearing loss, including 13 infants (0.2%) with bilateral moderate to profound sensorineural hearing loss (SNHL). Hearing rehabilitation with long-term follow-up was confirmed in 11 infants. Conclusions: In this hospital-based NHS program, the screening rate plateaued at ∼50% when the National Health Authority was not involved, but increased to ∼70% when the cost for low-income families was covered by the government. Among infants needing active hearing rehabilitation due to bilateral moderate to profound SNHL, 15% were lost to follow-up. These results demonstrate the need for a universal, mandatory NHS program to systematically register hearing-impaired infants within the government-sponsored public healthcare system.